A Clinical and Pathologic Exploration of Suspected Peritoneal Endometriotic Lesions. (November 2021) - Watkins, Jaclyn C.; DiVasta, Amy D.; Vitonis, Allison F.; Crum, Christopher P.; Laufer, Marc R.; Terry, Kathryn L.; Howitt, Brooke E.; Missmer, Stacey A.
Abstract : Endometriosis is generally histopathologically defined as the presence of at least 2 of the following: endometrial stroma, Müllerian epithelium, and/or hemosiderin-laden macrophages (HLM). Despite clinically evident endometriotic lesions, biopsies are frequently nondiagnostic. In this study, we conducted a large-scale review of biopsies of lesions clinically thought to represent endometriosis and correlate the histologic findings with clinical appearance to expand sensitivity of the pathologic definition of endometriosis, particularly in patients on hormonal therapy. In all, 112 biopsies from 78 patients (mean age=25, range 18–39 yr) were reviewed for histopathologic features suggestive of or diagnostic for endometriosis including the presence of endometrial stroma, Müllerian epithelium, dystrophic calcifications, HLM, chronic inflammation, adhesions, and vascular proliferation. Endometriosis was confirmed by pathologic criteria in 37 of 78 patients (47%). Biopsies from patients on hormonal therapy (n=62, 80%) were significantly less likely to meet pathologic criteria for endometriosis ( P =0.01). Nondiagnostic biopsies (70/112; 63%) frequently displayed HLM (20%), chronic inflammation (29%), dystrophic calcifications (26%), vascular proliferation (20%), or adhesions (20%) and were significantly more likely to have a vascular clinical appearance ( P =0.01). Diagnostic biopsies (42/112; 38%) were more likely to have a blue/black clinical appearance ( P =0.03), demonstrate HLM ( P =0.004), and display pseudodecidualization ( P =0.05). Patients with a high clinical suspicion of endometriosis have a range of histologic findings, with less than half meeting the current histopathologic criteria for diagnosing endometriosis. Given the heterogeneous histopathologic appearance, revision of the histologic criteria may be warranted with further exploration, particularly for lesions with predominantly vascular features.